Legislação brasileira sobre o uso do flúor na saúde pública - Souza, Bárbara Cecília Oliveira [UNESP]; Reis, Gustavo Sabbatine [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Fluoride employment - compound widely used in odontology to prevent caries - public health has your concentration, frequency and ways of using regulated by laws, decrees, resolutions and ordinances, so that people can enjoy its benefits without health risks. The project developed by the Children's Dentistry Department of Social and Araçatuba Dental School - UNESP , exercised continuously since 2004 , promoting the maintenance of drinking water quality of the inhabitants of 40 municipalities of São Paulo northwest. The Brazilian Constitution has Decree No. 76.872 of December 22, 1975 in which “regulates Law No. 6.050, of May 24, 1974, which provides for water fluoridation in public water supply systems”. Thus consolidating the need for the use of this technology public health and the importance of their knowledge by health professionals to improve the population's quality of life.

O emprego do flúor – composto muito utilizado em odontologia na prevenção da doença cárie - tem sua concentração, frequência e formas de uso regulamentado por leis, decretos, resoluções e portarias, para que a população possa usufruir dos seus efeitos benéficos, sem riscos para a saúde. O projeto desenvolvido pelo Departamento de Odontologia Infantil e Social da Faculdade de Odontologia de Araçatuba – UNESP, exercido continuamente desde 2004, promove a manutenção da qualidade da água de consumo dos habitantes de 40 municípios do noroeste paulista. A Constituição Brasileira conta com o Decreto N° 76.872 de 22 de dezembro de 1975 em que “regulamenta a Lei N°6.050, de 24 de maio de 1974, que dispõe sobre a fluoretação da água em sistemas públicos de abastecimento”. Sedimentando assim a necessidade do emprego desta tecnologia de saúde publica e a importância do seu conhecimento pelos profissionais da área da saúde para a melhora da qualidade de vida da população.
Keywords: Fluoride in odontology; Legislation; Prevention of tooth decay; Flúor em odontologia; Legislação; Prevenção da cárie dentária